2018
DOI: 10.4049/jimmunol.1601765
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Glycolysis-Driven Th17 Pathogenicity and Regulatory T Cell Stability by Cdc42

Abstract: A balance between Th17 cells and regulatory T cells (Tregs) is important for host immunity and immune tolerance. The underlying molecular mechanisms remain poorly understood. Here we have identified Cdc42 as a central regulator of Th17/Treg balance. Deletion of Cdc42 in T cells enhanced Th17 differentiation but diminished induced Treg differentiation and suppressive function. Treg-specific deletion of Cdc42 decreased natural Tregs but increased effector T cells including Th17 cells. Notably, Cdc42-deficient Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 51 publications
(68 reference statements)
5
80
0
Order By: Relevance
“…We have previously shown that thymic deletion of Cdc42 beginning at an early stage of thymocyte development by LCK Cre impaired thymocyte development, peripheral CD4 + and CD8 + T cell homeostasis, and iTreg differentiation but enhanced CD4 + and CD8 + T cell activation and Th1/Th17 cell differentiation with no effect on Th2 cell . In this study, we show that post‐thymic deletion of Cdc42 by dLCK iCre had no effect on thymocyte development, CD4 + T cell homeostasis, CD8 + T cell activation, and Th1/Th17/iTreg differentiation, whereas it dampened CD8 + T cell homeostasis, CD4 + T cell activation and Th2 cell differentiation.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…We have previously shown that thymic deletion of Cdc42 beginning at an early stage of thymocyte development by LCK Cre impaired thymocyte development, peripheral CD4 + and CD8 + T cell homeostasis, and iTreg differentiation but enhanced CD4 + and CD8 + T cell activation and Th1/Th17 cell differentiation with no effect on Th2 cell . In this study, we show that post‐thymic deletion of Cdc42 by dLCK iCre had no effect on thymocyte development, CD4 + T cell homeostasis, CD8 + T cell activation, and Th1/Th17/iTreg differentiation, whereas it dampened CD8 + T cell homeostasis, CD4 + T cell activation and Th2 cell differentiation.…”
Section: Discussionmentioning
confidence: 46%
“…We have previously shown that thymic deletion of Cdc42 beginning at an early stage of thymocyte development by LCK Cre impaired thymocyte development, peripheral CD4 + and CD8 + T cell homeostasis, and iTreg differentiation but enhanced CD4 + and CD8 + T cell activation and Th1/Th17 cell differentiation with no effect on Th2 cell. [17][18][19] In this study, we show that post-thymic deletion of Cdc42 by dLCK iCre had no effect on thymocyte development, CD4 + T cell Our transcriptome analysis found that Cdc42-deficient Th2 cells had increased mRNA expression of STAT4, indicative of Th1 reprogramming, 1 and of Foxp3, indicative of Treg reprogramming. 3,11 However, we did not detect alterations in protein expression of Th1 cytokine IFN-γ and Foxp3 in Cdc42-deficient Th2 cells ( Figure S6D and E), suggesting that the increased mRNA expression of STAT4…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Glycolysis deprivation was found to impair Th17 differentiation dramatically, while defective glycolysis supported the development of Treg cells. Replacement of glucose with galactose, treatment with 2-DG (an inhibitor of hexokinase, the first rate-limiting enzyme of glycolysis), and lack of HIF1α, Cdc42, ICER, and mTOR (crucial regulators of T cell glycolytic metabolism) all resulted in diminished Th17 development but enhanced Treg cell differentiation (16)(17)(18)(19)(20). Conversely, inhibition of fatty acid oxidation results in diminished differentiation to Th17 cells, but increased development of Tregs (21).…”
Section: Metabolic Control Of Th17/treg Balancementioning
confidence: 99%